Crime is in the Air: The Contemporaneous Relationship between Air Pollution and Crime - Malvina Bondy; Sefi Roth; Lutz Sager (Institute of Labor Economics (IZA), 2018)
Many empirical studies have examined various determinants of crime. However, the link between crime and air pollution has been surprisingly overlooked despite several potential pathways. In this paper, we study whether exposure to ambient air pollution affects crime by using daily administrative data for the years 2004-05 in London. For identification, we mainly rely on the panel structure of the data to estimate models with ward fixed effects. We complement our main analysis with an instrumental variable approach where we use wind direction as an exogenous shock to local air pollution concentrations. We find that elevated levels of air pollution have a positive and statistically significant impact on overall crime and that the effect is stronger for types of crime which tend to be less severe. We formally explore the underlying mechanism for our finding and conclude that the effect of air pollution on crime is likely mediated by higher discounting of future punishment. Importantly, we also find that these effects are present at levels which are well below current regulatory standards and that the effect of air pollution on crime appears to be unevenly distributed across the income distribution. Overall, our results suggest that reducing air pollution in urban areas may be a cost effective measure to reduce crime.
Keywords: H23; K42; Q53; 330; air pollution; crime; economic incentives